Exploring the application of mind map to enhance students' creative thinking / Jin Ruixuan ... [et al.] - Jin, Ruixuan; Narayanan, Geethanjali; Majid, Sheikha; Lin, Chenhui (Universiti Teknologi MARA Cawangan Sarawak, 2024)
As a visual thinking tool, a mind map can help people structure complex information and knowledge, stimulate and link new ideas, and thus improve creative thinking. Although there are studies on creative thinking and using mind maps, there are only a few studies in higher learning context. This paper mainly discusses the application of mind mapping in innovation and entrepreneurship courses in higher vocational colleges and explores the influence of mind mapping in improving students' creative thinking. This paper is based on a qualitative study using document analysis. The study includes results from three consecutive lessons where the mind maps and the products from each lesson were analyzed. The three assignments were analyzed to explore the impact of mind mapping on students' creative thinking and whether it could enhance students' creativity. Each mind map represents the knowledge of the students on the given topic. Students who have more knowledge would have more branches. This, in turn, also explains the creativity of the students' thinking. The creative students would add branches that are different from the norm. This also shows how these students view the topic and the world. Although the topic is related to innovation and entrepreneurship courses in higher vocational colleges and universities, the perception of the topic and how to break down ideas exhibit their creative thinking ability. This study proposes directions for future research intending to explore further and optimize the application of mind mapping in innovation and entrepreneurship courses in higher vocational colleges and universities to promote better the cultivation of students' innovation ability and entrepreneurship. This study will help the innovation and entrepreneurship courses in higher vocational colleges and universities utilize mind mapping more deeply and extensively to improve students' creative thinking. This will help improve students' creative and entrepreneurial abilities and contribute to the promotion of innovation and development in education.